PENGARUH KEPUASAN KERJA, SIKAP KERJA DAN WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN: Studi Kasus Pada PT Dana Purna Investama Jakarta - Natasya Tsurayya Lubna (2022)
This research was conducted to examine the effect of job satisfaction, work attitude, and work-life balance on employee performance using quantitative methods. The independent variables in this study are job satisfaction, work attitudes, and work-life balance and the dependent variable is employee performance. This research was conducted on employees of PT Dana Purna Investama Jakarta who were placed in KCU Bank BCA Regional Office 10 which consisted of 8 KCUs with a population of 184 employees. The sampling method in this study used the proportionate stratified random sampling method with 122 employees. The data for the research was obtained by distributing digital questionnaires in the form of a google form. By using the SmartPLS 3.0 application and the simultaneous F-test, this study reveals that job satisfaction partially does not have a significant effect on the performance of PT Dana Purna Investama Jakarta employees, work attitudes partially have a positive and significant effect on employee performance at PT Dana Purna Investama Jakarta., partially work-life balance has a positive and significant impact on the performance of employees of PT Dana Purna Investama Jakarta, as well as job satisfaction, work attitudes, and work-life balance together or simultaneously have a positive and significant influence on the performance of employees of PT Dana Purna Investama Jakarta. Keywords : Job Satisfaction, Work Attitudes, Work-Life Balance, Job Performance.